IMPLEMENTASI MITIGASI RISIKO PEMBIAYAAN DI BMT MANDIRI SEJAHTERA - Nasyiatul Farida; Ahlul Maghfiroh; Siti Roufah (IZZI: Jurnal Ekonomi Islam, 2022)
Understanding the risks involved in financing is important because it can cause losses to the organization, which will reduce profits. The distribution of financing carried out by BMT needs to have good and proper procedures in order to minimize the risk of loss from the initial application, the contract process, and the realization of funds. In this study, the researcher used a qualitative approach and the research was a case study. The data used were primary and secondary, collected through observation, interviews, and documentation. The analysis included data reduction, display, and verification. The results showed that BMT Mandiri Sejahtera had mitigated financing risks well by strengthening its human resources through training and analyzing the business conditions of its customers to prevent defaults on installments.